REXIC project: retrospective cross-sectional study of documentation of informed consent for research biobanking in a public research and teaching hospital - Marta Nobile; Elena Garavelli; Barbara Gagliardi; Silvia Giovanelli; Paolo Rebulla; Concetta Caccami; Diego Iemmi; Federico Saibene; Silvana Castaldi (SAGE Publishing, 2013)
Background. The Center for Transfusion Medicine, Cell Therapy and Cryobiology, Milan, Northern Italy, is the headquarter of the POLI-MI biobank. It co-ordinates the biobank activities of the Fondazione Ca' Granda Ospedale Maggiore Policlinico of Milan. Such activities require specific safeguarding of donors' rights and protection of sensitive and genetic data. The Fondazione Ca' Granda Ospedale Maggiore Policlinico has set up a project on informed consent with the aim of developing awareness and understanding of this issue. Within this project, it has been decided to evaluate how consent for biobanking material is expressed. Design and methods. The aim of the study was to evaluate the quality and completeness of consent to biobanking in the POLI-MI biobank. This was a retrospective study carried out in 2012 on samples of consent declarations collected by biobank units in 2011. Some units used a single, standard consent model available from a previous POLI-MI biobank workgroup. Other units used models which had been previouly formulated. Evaluation was made using a form that indicated the essential elements of consent. Results. A total of 48 consent declarations were collected using the single, standard model and 84 were collected using other models. The consent declarations that used the single, standard model were found to be the most complete and were filled in better than other models. Conclusions. Progressive adoption of a simple, standard consent model is expected to improve the quality of consent acquisition. Regular audit of the compliance of consent practices with ethical and legal requirements is mandatory to improve the quality of research biobanking.